Electrochemical characteristics of silicon-metals coated graphites for anode materials of lithium secondary batteries - Kim, In-Chul; Byun, Dongjin; Lee, Joong Kee (SPRINGER, 2006)
Four kinds of silicon-metals (Cu, Ni, Sn)-graphite composites for anode active materials of lithium secondary batteries were prepared by sequential employment of PECVD (Plasma enhance chemical vapor deposition) and RF(Radio-frequency)-magnetron sputtering method. The silicon-copper-graphite composite showed the highest reversible capacity and cyclability among the silicon-metal composite graphite samples prepared. The enhanced electrochemical performance of silicon-copper-graphite composite is attributed to the formation of copper silicide on the surface of graphite. The copper silicide plays an important role as a buffering layer against volume change of silicon during the intercalation/deintercalation due to the chemical bonding of silicon and copper, and has lower interfacial impedance than that of other silicon-metal-graphite composites which may lead to low irreversible capacity.